Professional Papervision3D - Lively, Michael (Wrox programmer to programmer, 2010)
Professional Papervision3D describes how Papervision3D works and how real world applications are built, with a clear look at essential topics such as building websites and games, creating virtual tours, and Adobe's Flash 10. Readers learn important techniques through hands-on applications, and build on those skills as the book progresses. The companion website contains all code examples, video step-by-step explanations, and a collada repository.